PENGGUNAAN ANALISIS KRITIS UNTUK MENINGKATKAN KEMAMPUAN METAKOGNITIF PADA POKOK BAHASAN PENGELOLAAN LINGKUNGAN SISWA SMP - Marheny Lukitasari; Joko Widiyanto; Yenisha Maidha Yahya (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
This aims to determine the use of critical analysis to improve metacognitive skills of students of SMP Negeri 2 Karangrejo on Topic Environmental Management. This research is a qualitative descriptive study is to describe the data obtained by identifying metacognitive skills of students through the use of critical analysis. This research was done in SMPN 2 Karangrejo class VII semester 2015. Researchers used 26 students as respondents and one expert as an observer. Data collection techniques is data metacognitive skills based on critical analysis of the workmanship scores of students, which is interpreted in the assessment of the level of metacognitive skills. The data analysis technique used is descriptive qualitative. Results of the study are: (1) the use of critical analysis showed an increase in metacognitive abilities of students seen from the averagevalue of critical analysis in the first meeting and the second meeting, namely 50.09 and 66.13 (2) the observation of the quality of the implementation of learning have criteria " very good "seen from the average of the two meetings by an average score of 4.5 and a percentage of 91%.